Aktivitas Antibakteri dan Antijamur Fraksi Etil Asetat Kulit Buah Jeruk Manis (Citrus sinensis (L.) Osbeck) - Octaviani, Melzi; Masnun, Lidiatil; Nasution, Musyirna Rahmah; Susanti, Emma; Utami, Rahayu; Furi, Mustika (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
The sweet orange (Citrus sinensis (L.) Osbeck) is a popular fruit. The part of the sweet orange that is consumed is only the fruit flesh, while the orange peel is only thrown away and not utilized. The sweet orange peel contains several secondary metabolites, namely alkaloids, flavonoids, tannins, phenols, saponins, and steroids, which have antimicrobial properties. This study aims to determine the effect of the concentration of the ethyl acetate fraction of sweet orange peel on antibacterial and antifungal activity in Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Salmonella typhi, and Candida albicans fungi using the disc diffusion method. The ethyl acetate fraction was prepared in several concentration series, namely 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.5625% w/v. The results obtained showed that all concentrations of the ethyl acetate fraction series showed activity in inhibiting the growth of Salmonella typhi bacteria. Series concentrations of 3.125% to 50% have activity in inhibiting the growth of Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Candida albicans fungi. The results of the data analysis using statistical one-way ANOVA showed that the antibacterial and antifungal activities between the concentration series were significantly different (p<0.05) from the negative control.